Cross-national analysis of the short- and longer-term effects of conditions at labor market entry - Christian König; Thomas Biegert; Jan Paul Heisig; Heike Solga (INVEST Research Flagship Centre / University of Turku, 2025)
This report uses data from the European Union Labour Force Survey (EU-LFS) to examine whether poor macro-economic conditions at labor market entry increase the risk of labor market exclusion (non-employment) and insecurity (temporary contracts and low-skilled jobs) 5 to 10 years after entry, and whether this differs by entrants' gender and education. The analyses are based on young adults who entered the labor market in Europe between 1994 and 2011, so that labor market outcomes are examined between 1999 and 2021. The analyses focus on the effects of unemployment rates at entry at the regional level, defined by the European regions (NUTS1 = regions with populations between 3 and 7 million inhabitants), which are closer to individuals' actual labor markets than the national level. The report also investigates the role of labor market institutions (employment protection legislation (EPL) for permanent employment and for temporary employment, and public spending on active and passive labor market policies (ALMP, PLMP)), that is, whether they increase or decrease the risk of labor market exclusion and insecurity due to poor economic conditions at entry.
Keywords: 330